The Effect of Green Packaging and Store Atmosphere on Purchase Intention for Fore Coffee Products in Surabaya - Rahmawati, Eka Putri; Dermawan, Rizky (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The coffee connoisseur index is rising by around 8% annually. Alongside the proliferation of coffee shops, the amount of plastic waste from packaging is also on the rise. Fore Coffee is innovating by using eco-friendly packaging to protect the environment. However, this does not guarantee an increase in Fore Coffee sales. One of Fore's strategies to boost sales is to create a unique and distinctive store atmosphere that sets it apart from other coffee shops. This study aims to examine the effect of green packaging and store atmosphere on consumer purchase intention. The research methodology employed is quantitative in nature. The study encompasses the population of Surabaya City residents. A non-probability sampling method, specifically purposive sampling, is utilized to select a sample of 96 respondents who identify as patrons of local coffee shops and are aware of Fore Coffee's environmentally friendly product concept. Smart-PLS version 3 serves as the statistical tool employed in this research. The findings of the study reveal that green packaging exerts a significantly positive impact on purchase intention, while store atmosphere also exhibits a significantly positive influence on purchase intention.